HANDLING THE ATTENTION SPAN OF GRADE 1 STUDENTS AT EQUALBRIGHT SCHOOL - Jessica Jessica; Iman Santoso (IKIP Siliwangi, 2022)
This article focused on the teachers' strategies in getting the grade 1 students' attention span at equalBright School. Since the students could not proceed classroom activities well, thus some strategies will be necessary. The aims of this article were to find out the teachers' strategies in getting students's attention span. This article will use qualitative research design in analyzing the teacher's strategies in getting grade 1 students' attention span at equalBright School. The teacher used four strategy in getting students' attention span, which are giving clear direction and asking student to repeat it, making learning interesting, setting the HOTS (Higher order thinking skills) and varying lesson presentations. In addition, there will be advantages by applying those strategies in the classroom, like helping the students to evaluate information rapidly, making connections between the lesson, fully engaged in the lesson, it is able to make an effective limiting teaching to make it not too long for the students. Keywords: Attention, SPAN, Equalbright School